2015
DOI: 10.1002/ejp.551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intra‐articular hyaluronic acid injection on immunohistochemical characterization of joint afferents in a rat model of knee osteoarthritis

Abstract: Intra-articular HA injections reduced the severity of OA, decreased mechanical hyperalgesia of the paw, but not weight-bearing asymmetry, and attenuated OA-associated up-regulation of CGRP, but not TrkA and ASIC3, in joint afferents. The modulatory effects of HA on joint afferents is one of the underlying mechanisms of the gap between HA residence time and duration of clinical efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…They reported that intra-articular HA injection reduced OA severity, decreased paw mechanical hyperalgesia, and attenuated OA-associated upregulation of calcitonin gene-related peptide (CGRP). However, no studies have investigated the effects of HA on pain relief in a model of ankle OA 42. In our study, significant mechanical hypersensitivity (ie, allodynia) was observed in the MIA rats, but not in the MIA-HA rats, 14 days after MIA injection.…”
Section: Discussionmentioning
confidence: 48%
“…They reported that intra-articular HA injection reduced OA severity, decreased paw mechanical hyperalgesia, and attenuated OA-associated upregulation of calcitonin gene-related peptide (CGRP). However, no studies have investigated the effects of HA on pain relief in a model of ankle OA 42. In our study, significant mechanical hypersensitivity (ie, allodynia) was observed in the MIA rats, but not in the MIA-HA rats, 14 days after MIA injection.…”
Section: Discussionmentioning
confidence: 48%
“…In an IA mono-iodoacetate (MIA) model of knee OA in rats, IA Supartz FX decreased pain-related behavior as well as the number of pain-transmitting cells in the dorsal root ganglion, as determined by marker for calcitonin gene-related peptide (CGRP). 30 Further in vitro experiments indicated that Supartz FX decreased COX-2 mRNA levels in synoviocytes and chondrocytes 5 , 23 (Suppl. Table S7).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, several animal studies on OA pain reported similar findings on the HA effect. Ikeuchi et al employed a monoiodoacetate (MIA)-induced OA pain model and found no significant difference in weight-bearing asymmetry in HA-treated rats [54]. Boettger et al also demonstrated in a rat bradykinin/PGE2 pain model that HA lost its antinociceptive efficacy (shown as weight-bearing asymmetry) from day 7 after injection [55].…”
Section: Discussionmentioning
confidence: 99%